Analisis Konten Media Sosial Instagram Bengkulu Info Sebagai Media Penyebaran Informasi Lokal - Effendi, Virgo; Narti , Sri; Dianthi , Martha Heriniazwi (CV. Era Digital Nusantara, 2024)
Instagram is a social media application that allows users to take photos, apply digital filters (effects to photos), and share them. This research aims to analyze the content of the Bengkulu Info Instagram social media as a medium for disseminating local information. This research is a qualitative research. Based on the Four Pillars Social Media Strategy Theory according to the theory of Lon Safko & David K Brake. The results of this research show that the entertainment content presented by @bengkuluinfo is interesting, varied, effective and unique and popular with consumers so that the audience does not feel bored and is entertained by up to date content. However, when presenting entertainment content, attention needs to be paid so that it is not excessive and out of context with the image that @bengkuluinfo has. The application of collaborative content on Instagram social media provides a positive opportunity for @bengkuluinfo on how to work together to make good things more effective and more efficient with the same goal, common perception, willingness to process, providing mutual benefits, honesty, compassion and the community. The information content uploaded by Instagram @bengkuluinfo has an interesting concept and the information provided in the content is very clear so that the content presented can make it easier for Instagram followers @bengkuluinfo to understand the content, and of course followers on Instagram can feel fulfilled by the information content provided. so that followers can clearly pay attention to the contents of the uploaded information content. The educational content analyzed in the post